Susceptibility of Multidrug-Resistant and Biofilm-Forming Uropathogens to Mexican Oregano Essential Oil - Karen Arely Zapién-Chavarría; Alejandro Plascencia-Terrazas; María Georgina Venegas-Ortega; Mauricio Varillas-Torres; Blanca Estela Rivera-Chavira; Jaime Raúl Adame-Gallegos; María Olga González-Rangel; Guadalupe Virginia Nevárez-Moorillón (MDPI AG, 2019)
Antibiotic resistance along with biofilm formation increases the difficulty for antibiotic therapy in urinary tract infections. Bioactive molecules derived from plants, such as those present in essential oils, can be used to treat bacterial infections. Oregano is one of the spices to have antimicrobial activity. Therefore, three Mexican oregano essential oils (two Lippia berlandieri Schauer and one Poliomintha longiflora) were tested for antimicrobial capacity against multidrug-resistant, biofilm-forming bacterial isolates. Clinical isolates from urinary tract infections were tested for antibiotic resistance. Multidrug-resistant isolates were evaluated for biofilm formation, and Mexican oregano antimicrobial effect was determined by the minimal inhibitory (CMI) and minimal bactericidal concentrations (CMB). The selected isolates were identified by molecular phylogenetic analysis. Sixty-one isolates were included in the study; twenty were characterized as multidrug-resistant and from those, six were strong biofilm formers. Three isolates were identified as Escherichia coli, two as Pseudomonas aeruginosa and one as Enterococcus faecalis based on the phylogenetic analysis of 16 S rRNA gene sequences. The antimicrobial effect was bactericidal; E. faecalis was the most susceptible (<200 mg/L CMI/CMB), and P. aeruginosa was the most resistant (>2,000 mg/L CMI/CMB). There was a range of 500-1000 mg/L (CMI/CMB) for the E. coli isolates. Mexican oregano essential oils demonstrated antimicrobial efficacy against multidrug-resistant clinical isolates.